Recovery of Anthraquinones from Morinda Elliptica Cell Culture via In Situ Adsorption Using Polymeric Adsorbents - Chiang, Lim (2007)
Morinda elliptica (Rubiaceae) cell suspension culture was used as a model system to understand the effects of in situ adsorption by polymeric adsorbents. The adsorption capacities of the adsorbents were determined and their equilibrium adsorption were fitted to Langmuir, Freundlich and Redlich-Petersen isotherms using linear and non-linear methods of analyses. The kinetic profiles of cell growth and anthraquinone (AQ) production were determined for cultures grown in intermediary (G) and production (P) medium strategies. Selection of the most suitable solvent was also carried out for effective recovery of AQ from the adsorbents. Co-cultivation of both untreated and pretreated adsorbents with G and P medium cultures were carried out to select a more biocompatible adsorbent that could enhance AQ production without affecting cell growth. The selected adsorbents were then further investigated for effective in situ adsorption factors in P medium strategies. High performance liquid chromatography (HPLC) was used for qualitative analyses of AQ constituents for extracts obtained from cells, culture medium and adsorbents. XAD-16 showed the highest capacity at 0.0424mg alizarin/mg adsorbents whereas XAD-4 and XAD-7 showed a capacity of 0.0113 and 0.0109mg alizarin/mg adsorbents at initial alizarin solution concentration of 200mg/L, respectively. Freundlich isotherm fitted well to both XAD-4 and XAD-7 whereas Langmuir isotherm gave the best correlation to XAD-16 over the concentration ranges studied. Ethanol was chosen as the eluting solvent with highest AQ recovery at 11.13mg/g, 5.20mg/g and 4.92mg/g eluted from XAD-4, XAD-7 and XAD-16, respectively. M. elliptica cell cultures achieved the highest biomass concentration at 36.79g/L on day 18 with 13.49mg/g DW intracellular AQ obtained in G medium strategy. In P medium strategy, the biomass concentration peaked on day 21 at 48.37g/L with intracellular AQ production recovered at 117.81mg/g DW. As 0.15g of both pretreated and untreated resins were added into cell cultures on day 15 and harvested on day 21, sodium acetate-pretreated XAD-4 stimulated AQ production to the highest extent in both G and P medium cultures. In G medium cultures, 25.67mg/g intracellular AQ was obtained, which was 1.4-fold to control. 1.04mg/L AQ recovered from the culture medium was 1.6-fold to control whereas 0.97mg/g AQ was obtained from the resins. Cell growth was comparable to control. In P medium cultures, cell growth was retarded where 15.43g/L biomass concentration were obtained, which was 23% lower than control. However, as high as 76.21mg/g intracellular AQ was obtained, which marked 1.4-fold increase to control. While 12.21mg/L extracellular AQ recovered was 6.6-fold higher than control, 1.08mg/g AQ was recovered from the resins. When treated with 0.15g sodium acetate-pretreated XAD-4 on day 18, cell growth was comparable to control after 6 days of co-cultivation. 123.83mg/g DW intracellular AQ was obtained, which was 1.7-fold to control. 14.34mg/L extracellular AQ was recovered, which was 11-fold to control, whereas 2.7mg/g AQ was desorbed from the resins. When the factors were further studied, as high as 68.99mg/g DW intracellular AQ was obtained when cultures were treated with 0.25g XAD-4 on day 18 and harvested on day 24. This was 1.2-fold higher than control. 6.32mg/L extracellular AQ was recovered, which was comparable to control, while 0.52mg/g AQ was desorbed from the resins. However, cell growth was reduced 9.5% to 34.77g/L compared to control. A few types of AQ constituents were detected from the cells, culture medium and XAD-4 resins through qualitative HPLC analyses. Four different types of AQ compound were identified. While only rubiadin-1-methyl ether was detected in the cells, both damnacanthal and nordamnacanthal were detected from the culture medium whereas lucidin-ω-methyl ether was detected from XAD-4 resins. Numerous unidentified peaks were also detected frequently from the AQ extracts.